Vibrational Spectra and ab initio Studies of L-Prolyl L-Isoleucine - Sampath Krishnan, S.; Santhana Krishnan, V.; Swarna Sowmya, N.; Kumutha, R. (Asian Journal of Chemistry, 2012)
Quantum mechanical calculation of energies, geometries and vibrational wave numbers of L-prolyl L-isoleucine has been carried out by using density functional theory (DFT/B3LYP) method with 6.31G (d,p) as basic set. The optimized geometrical parameters obtained by DFT calculations are found to be good agreement with experimental X-ray data. The best level of theory in order to reproduce the experimental wave numbers is B3LYP method with the 6.31G(d,p) basis set. The difference between the observed and scaled wave number values of most of the fundamentals is very small. An interpretation of the infrared and Raman spectra has also been reported. The entropy of the compound under study is also performed.